Development of a Massive Open Online Course on Reference Management - Widiyanto, Widiyanto; Mujiono, Mujiono (Journal of Nonformal Education, 2026)
Background - In the digital age and increasing access to scientific information, the ability to effectively manage references is becoming an important skill for students, researchers, and academics. The development of information technology has presented various reference management software that can help users in organizing literature, automating the citation process, and minimizing errors in writing scientific papers. However, there are still many academics who have not mastered the optimal use of the application due to the limitations of training, the complexity of application features, and the limited structured learning resources. Research Urgency - With the increasing demand for scientific publications and the need for quality academic writing, accessible and systematic learning media are needed to improve reference management competency. Massive Open Online Courses (MOOCs) offer an open, flexible, and accessible online learning environment for participants from a wide variety of backgrounds. Therefore, developing a MOOC on reference management is crucial to provide structured learning resources, enhance learning independence, and assist academics and researchers in managing citations and bibliographies more efficiently and accurately. Research Objectives - This study aims to develop a MOOC on Reference Management. Research Method - Utilizing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the research has reached the development phase. In the analysis phase, learning needs were identified through interviews with students, lecturers, and journal management practitioners. The interviews revealed that participants required a deeper understanding of reference management software, proper citation principles, and efficient reference management techniques. In the design phase, the focus was on formulating learning competencies, constructing a competency map, and designing materials and assignments that support the achievement of learning objectives. Research Findings - The validation results indicated a very high level of validity, with a percentage of 90% for content experts and 88% for media experts, placing this MOOC in the "highly valid" category and ready for use without revision. The user trial involved students, lecturers, and practitioners, who provided positive feedback regarding accuracy, time efficiency, and cost-effectiveness. Research Conclusion - Based on these findings, the Reference Management MOOC is recommended for implementation with ongoing evaluation and feedback to ensure its relevance and effectiveness. Research Novelty/Contribution - The development of a MOOC specifically designed to improve reference management competency in scientific writing. This MOOC provides structured, flexible, and widely accessible learning, thus providing a more effective training alternative than conventional training.